Agricultural dust explosions in 2003 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were seven dust explosions reported in the U.S. in 2003 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Mavis Rogers, FGIS-USDA. This compares to 8 in 2002 and a tenyear average of 11.5 explosions.
Keywords: Grain dust; Dust explosions